Segmented turning - Keeling, Dennis (Taunton Press, 2012)
"An easy-to-access, photographic guide to the essential techniques for learning closed segmented, open segmented, and ornamental segmented turning. Also, includes 10 projects for both new and advanced segmented turners"--